Răspuns :
Răspuns: [tex]\color {CC0000}\Large\boxed{ \bf \dfrac{61}{16}}~~~sau~~~\boxed{ \bf 3\dfrac{13}{16}}[/tex]
Explicație pas cu pas:
Salutare!
[tex]\color{red}\Large \boxed{\boxed{\bf Formula: \bigg(a-b\bigg)\cdot \bigg(a+b \bigg) = a^{2} -b^{2}}}[/tex]
[tex]\large \bf \Bigg(2-\dfrac{\sqrt{3} }{4} \Bigg)\cdot \Bigg(2+\dfrac{\sqrt{3} }{4} \Bigg) =\bigg(2 \bigg)^{2}- \Bigg(\dfrac{\sqrt{3} }{4} \Bigg)^{2} =[/tex]
[tex]\large \bf 4-\dfrac{(\sqrt{3} )^{2}}{4^{2}} = 4-\dfrac{3}{16} = \dfrac{(16\cdot 4-3)}{16} =\dfrac{64-3}{16} =[/tex]
[tex]\color {blue}\large\boxed{ \bf \dfrac{61}{16}}~~~sau~~~\boxed{ \bf 3\dfrac{13}{16}}[/tex]
Bafta multa!
PS: Daca esti pe telefon, te rog sa glisezi spre stânga pentru a vedea rezolvarea completa.
==pav38==